Respuesta :

Answer:

[tex]\angle BDA = 72^{\circ}[/tex]

[tex]\angle DAB = 36^{\circ}[/tex]

[tex]\angle BDC = 108^{\circ}[/tex]

[tex]\angle BCD = 36^{\circ}[/tex]

[tex]\angle DBC = 36^{\circ}[/tex]

Step-by-step explanation:

Given

[tex]\angle ABD = 72^{\circ}[/tex]  

Required

Determine the missing angles

Since AB = AD, then:

[tex]\angle ABD = \angle BDA[/tex] --- Base angles of an isosceles triangle

Hence:

[tex]\angle ABD = \angle BDA = 72^{\circ}[/tex]

[tex]\angle ABD + \angle BDA + \angle DAB = 180^{\circ}[/tex] --- angles in a triangle

[tex]72^{\circ} + 72^{\circ} + \angle DAB = 180^{\circ}[/tex]

[tex]144^{\circ} + \angle DAB = 180^{\circ}[/tex]

Collect Like Terms

[tex]\angle DAB = 180^{\circ} - 144^{\circ}[/tex]

[tex]\angle DAB = 36^{\circ}[/tex]

[tex]\angle BDA + \angle BDC = 180^{\circ}[/tex] --- angle on a straight line

[tex]72^{\circ} + \angle BDC = 180^{\circ}[/tex]

[tex]\angle BDC = 180^{\circ} - 72^{\circ}[/tex]

[tex]\angle BDC = 108^{\circ}[/tex]

Since ABC is isosceles, then:

[tex]\angle DAB = \angle BCD = 36^{\circ}[/tex] --- base angle of isosceles

[tex]\angle BCD = 36^{\circ}[/tex]

Lastly:

[tex]\angle BCD + \angle BDC + \angle DBC = 180^{\circ}[/tex]

[tex]36^{\circ} + 108^{\circ} + \angle DBC = 180^{\circ}[/tex]

[tex]\angle DBC = 180^{\circ} - 36^{\circ} - 108^{\circ}[/tex]

[tex]\angle DBC = 36^{\circ}[/tex]

See attachment

Ver imagen MrRoyal